European Stroke Organisation (ESO) guidelines for the management of temperature in patients with acute ischemic sf kotroke: $hGeorge Ntaios, Tomasz Dziedzic, Patrik Michel, Vasileios Papavasileiou, Jesper Petersson, Dimitre Staykov, Brenda Thomas, Thorsten Steiner for the European Stroke Organisation - Ntaios, George; Steiner, Thorsten (International journal of stroke, 2015)
Background Hyperthermia is a frequent complication in patients with acute ischemic stroke. On the other hand, therapeutically induced hypothermia has shown prom...
Gesehen am 17.06.2020